Benefits from Below: Silicon Supplementation Maintains Legume Productivity under Predicted Climate Change Scenarios - Johnson, Scott N.; Ryalls, James M. W.; Gherlenda, Andrew N.; Frew, Adam; Hartley, Susan E. (Frontiers in Plant Science, 2018)
Many studies demonstrate that elevated atmospheric carbon dioxide concentrations (eCO2) can promote root nodulation and biological nitrogen fixation (BNF) in legumes such as lucerne (Medicago sativa). But when elevated temperature (eT) conditions are applied in tandem with eCO¬2, a more realistic scenario for future climate change, the positive effects of eCO2 on nodulation and BNF in M. sativa are often much reduced. Silicon (Si) supplementation of M. sativa has also been reported to promote root nodulation and BNF, so could potentially restore the positive effects of eCO2 under eT. Increased nitrogen availability, however, could also increase host suitability for aphid pests, potentially negating any benefit. We applied eCO2 (+240ppm) and eT (+4ºC), separately and in combination, to M. sativa growing in Si supplemented (Si+) and un-supplemented soil (Si-) to determine whether Si moderated the effects of eCO2 and eT. Plants were either inoculated with the aphid Acyrthosiphon pisum or insect-free. In Si- soils, eCO2 stimulated plant growth by 67% and nodulation by 42%, respectively, whereas eT reduced these parameters by 26% and 48%, respectively. Aphids broadly mirrored these effects on Si- plants, increasing colonization rates under eCO2 and performing much worse (reduced abundance and colonization) under eT when compared to ambient conditions, confirming our hypothesized link between root nodulation, plant growth and pest performance. Examined across all CO2 and temperature regimes, Si supplementation promoted plant growth (+93%), and root nodulation (+50%). Acyrthosiphon pisum abundance declined sharply under eT conditions and was largely unaffected by Si supplementation. In conclusion, supplementing M. sativa with Si had consistent positive effects on plant growth and nodulation under different CO2 and temperature scenarios. These findings offer potential for using Si supplementation to maintain legume productivity under predicted climate change scenarios without making legumes more susceptible to insect pests.